Evidence of injection drug use in Kisumu, Kenya: Implications for HIV prevention. (1st June 2015) - Syvertsen, Jennifer L.; Agot, Kawango; Ohaga, Spala; Strathdee, Steffanie A.; Camlin, Carol S.; Omanga, Eunice; Odonde, Petronilla; Rota, Grace; Akoth, Kelvin; Peng, Juan; Wagner, Karla D.
Highlights: We provide the first descriptive analysis of injection drug use in Kisumu, western Kenya. Women had four times the odds of self-reporting HIV infection. Sexual and injection drug-related risk factors were associated with being HIV positive. Harm reduction programs are urgently needed in emergent drug markets in Kenya. Abstract: Background: Injection drug use is increasingly contributing to the HIV epidemic across sub-Saharan Africa. This paper provides the first descriptive analysis of injection drug use in western Kenya, where HIV prevalence is already highest in the nation at 15.1%. Methods: We draw on quantitative data from a study of injection drug use in Kisumu, Kenya. We generated descriptive statistics on socio-demographics, sexual characteristics, and drug-related behaviors. Logistic regression models were adjusted for sex to identify correlates of self-reported HIV positive status. Results: Of 151 participants, mean age was 28.8 years, 84% ( n = 127) were male, and overall self-reported HIV prevalence reached 19.4%. Women had greater than four times the odds of being HIV positive relative to men (Odds Ratio [OR] 4.5, CI: 1.7, 11.8, p = .003). Controlling for sex, ever experiencing STI symptoms (Adjusted Odds ratio [AOR] 4.6, 95% CI 1.7, 12.0, p = .002) and sharing needles or syringes due to lack of access (AOR 3.6, 95% CI 1.2, 10.5, p = .02) were significantly associated with HIV positive status. Lower education (AOR 2.3, 95% CI 0.9, 5.6, p = .08), trading sex for drugs (AOR 2.8, 95% CI 0.9, 8.8, p = .08), being injected by a peddler (AOR 2.9, 95% CI 1.0, 8.5, p = .05), and injecting heroin (AOR 2.3, 95% CI 1.0, 5.7, p = .06), were marginally associated with HIV. Conclusions: This exploratory study identified patterns of unsafe drug injection and concurrent sexual risk in western Kenya, yet few resources are currently available to address addiction or injection-related harm. Expanded research, surveillance, and gender sensitive programming are needed.